Colonial violence and anticolonial primary resistance in selected novels of Le Clézio (2017)
Postcolonial writers – from the formerly colonised countries – usually feel more entitled to offer narratives of local resistance against the domination and exploitation of Western imperialism. Existing literatures have revealed that classical French writers with obvious anti-colonial agenda were not exempt from Eurocentric hegemonic penchant. However, much more need to be said about contemporary French writers who wrote about their colonial experiences as victims. This paper focuses on the experiences of violence and anticolonial resistance, mainly in the colonised territories around Onitsha, South-East Nigeria. The study applies Fanon’s principles of violence and resistance which preconise defiance within the anticolonial struggle with a view to establishing the anti-colonial reactions permeating Le Clézio’s novels, namely Chercheur d’or, Onitsha and L’Africain. The novels present the sympathy of European narrators towards various forms of defiance by the oppressed natives, both individual and collective resistance, through strikes, boycotts and murder. They demonise the colonisers who used excessive force to quash local revolts. Narratives of exploitation and fraud slur the colonisers, who could be qualified as mere capitalists. The texts incriminate capitalists, in the guise of colonial powers, with the post-independence woes of African countries and reveal the conspiracy of Western powers to infantilise and vilify newly independent countries. These contemporary narratives of anticolonial resistance foreground Le Clézio as an enforcer of social justice in a globalized world.